Older drivers retiring from the road: an application of the selection, optimization, and compensation model. - Pickard JG; Tan J; Morrow-Howell N; Jung Y (Journal of Human Behavior in the Social Environment, 2009)
Purpose: This study uses the selection, optimization, and compensation (SOC) model to compare older adults who have given up driving, those who still drive, and those who drive less to identify differences in the three groups. Design and Methods: This cross-sectional study of 281 older adults is part of the Naturally Occurring Retirement Community Demonstration Project. Study participants completed interviews that included questions on demographics, health and functioning, mental health, social support, and current levels of engagement in activities including current driving status. Results: Data suggest that driving retirement is a process and that a substantial number of people are in the transitional stage, where they are less functional than those who still drive and more similar to those who have retired from the road. Implications: Given the similarity of those who drive less to those who have given up driving, front-line professionals and policy makers must work together to ease the transition to driving retirement for those without adequate ability to effectively compensate for their inability to continue to drive safely.